Nanocomposite Coatings Based on Polyvinyl Alcohol and Montmorillonite for High-Barrier Food Packaging - Schiessl, Stefan; Kucukpinar, Esra; Cros, Stéphane; Miesbauer, Oliver; Langowski, Horst-Christian; Eisner, Peter (Frontiers in Nutrition, 2022)
Materials with high barrier properties against oxygen are required for the packaging of many sensitive foods. Since commodity polymers lack these properties, additional barrier materials are used in plastic-based barrier packaging. These are usually more expensive than commodity polymers and, in higher fractions, also make recycling more difficult. Current developments therefore aim at barrier layers that are as thin as possible, but retain the barrier properties. One approach is to incorporate nanoparticles into these layers. In this paper, the barrier properties of nanocomposite coatings, consisting of unmodified polyvinyl alcohol (PVA), and dispersed stick-shaped or platelet-shaped silicate nanoparticles, were investigated. The PVA was dissolved in aqueous nanoparticle dispersions, which were prepared by mechanical shearing, to produce the so-called "nanolacquer". Nanolacquers with nanoparticle concentrations of 7, 30, and 47 vol% with respect to PVA were applied in a single process step with k-bar on a polypropylene substrate film. The integration of 30 vol% platelet-shaped montmorillonite enhances the barrier performance in comparison to pure PVA by a factor of 12 and 17 for oxygen and helium, respectively,. Scanning electron microscopy (SEM) shows a homogeneous distribution and a parallel alignment of the nanoparticles within the coated layer. An increase in the crystallinity of PVA was observed due to the nanoparticle integration as demonstrated by x-ray diffraction (XRD) measurements. The investigation by Fourier transform infrared (FTIR) spectroscopy and the activation energy of the permeation coefficient indicate an interaction between the nanoparticles and the PVA. The theoretically calculated values for barrier enhancement accord well with the experimental values, which emphasizes that the gas barrier improvement for oxygen and helium is mainly dominated by the tortuous path effect.